A bibliometric and visualized analysis of research on mitochondria in myocardial ischemia from 2015 to 2024 - Yang Lu; Fanghe Li; Qiong Wu; Qingteng Zhai; Xinyi Li; Weibin Xie; Shuwen Guo; Shuwen Guo; Kuo Gao (Frontiers in Cardiovascular Medicine, 2025)
BackgroundMitochondria, as the powerhouse of myocardial energy metabolism, have garnered considerable interest in the realm of myocardial ischemia (MI) therapy research. The purpose of this study is to illustrate the hot spots and frontiers of mitochondrial research in MI in the past decade through bibliometric analysis.MethodsBoth articles and reviews of mitochondrial research in MI from 2015 to 2024 were retrieved from the Web of Science Core Collection database. Bibliometric analysis was performed mainly using CiteSpace and VOSviewer.ResultsThe analysis encompassed 4,387 papers. The annual publications exhibited a significant increasing trend, rising from 342 publications in 2015 to 541 publications in 2024. China, the United States of America, and Germany emerged as the top three contributors to MI related mitochondria studies. The Air Force Medical University, China, was the leading publisher. Chattipakorn, Nipon (Chiang Mai University), Chattipakorn, Siriporn C (Chiang Mai University), Zhou, Hao (Zhejiang University) were the top three most active and influential scholars based on the H-index. International Journal of Molecular Sciences was the most co-cited journal in this field. Until 2024, the keywords with the strongest citation bursts included mitophagy, transplantation, homeostasis, and myocardial ischemia-reperfusion. The current research trend is to translate mitochondria-related diagnostic and therapeutic drugs for MI into the clinic.ConclusionsExploring MI from a mitochondrial perspective has great potential. By revealing the knowledge structure of this field, this study helps to provide scholars in related fields with a comprehensive understanding of the field and develop collaborations.